VERBAL AND NOMINAL COMPARISONS IN POLISH AND UKRAINIAN PHRASEOLOGY - Демьяненко, Наталия (Acta Neophilologica, 2015)
Fixed comparisons are the source of idiomatic comparisons. Comparative phraseology demonstrates a wide range of culturally conditioned ideas of Poles and Ukrainians and the compositions of phraseological unit core components are embedded in culturally-rooted systems. The aim of this study was to identify intelligence and analyze Polish phraseological units with the comparison component and find their equivalents in the Ukrainian language. Basic principles concerning the structuring of Polish comparative phrases are similar to those in Ukrainian, although there are examples where the grammatical form of a phraseological unit or its part does not match the grammatical equivalent category in the Ukrainian language.